Understanding social dynamics towards circular fashion initiatives in Indonesia through actor-network-theory - Rahayu Budhi Handayani; Olivia Gondoputranto (Sustinere: Journal of Environment and Sustainability)
Circular fashion represents a practical effort to achieve a more sustainable fashion industry. The Indonesia Circular Economy National Roadmap and Action Plan 2025-2045 identifies the textile and fashion sector as one of its top priority sectors for transitioning to circularity. Circular fashion emphasizes a shift from the traditional linear system, take-make-dispose, to a comprehensive approach in which fashion items are intended to last longer, be reusable, and be recycled back into the biosphere at the end of their lifecycle. This transition requires a systemic transformation throughout the entire value chain. This article explores the social dynamics through which both human and non-human actors drive circular fashion initiatives in Indonesia, employing actor-network theory (ANT) as its methodological framework. Using a qualitative approach, comprising focused ethnographic observations, interviews, and document analysis, the study explores two key contexts, the Circular Fashion Partnership Indonesia (event setting) and two design studios in Yogyakarta (real-world setting). The findings reveal that the event serve to foster network formation and vision alignment, while the design studios translate these visions into practical, localized practices. ANT highlights the interconnected feedback loops within networks that integrate human actors (e.g., designers, business, government, community/consumers, academia, media) and non-human actors (e.g., materials, technology, policies), all of which influence both the event-based and real-world settings. Understanding the social dynamics shaped by these networked interactions is essential for the successful implementation of circular fashion practices in Indonesia. This study offers insights for stakeholders to strengthen collaboration, anticipate potential challenges, and develop strategies to promote sustainability through circular fashion.